Schwannoma of oral tongue - C. Viswanatha, Sumana; Raghavan, Nisheena (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Schwannomas also known as Neurilemmoma, are benign encapsulated slow growing tumors, which arise from Schwann cells of the peripheral nerve sheath. They usually occur in the head and neck region, but rarely in the oral cavity. We report a case of Schwannoma of the oral tongue in a 49-year-old male patient, who presented with a slow growing, painless lesion involving left side of the dorsum of the oral tongue. Patient underwent Magnetic Resonance Imaging with contrast followed by complete surgical excision. Histopathological and Immunohistochemical examination confirmed the diagnosis.